(untitled) (Academia Science Repository, 2023)
In clinical practice, both overdiagnosis and underdiagnosis of DE are often observed. To make a correct diagnosis, it is necessary, along with obtaining detailed medical history data, a thorough examination of the neurological status and the state of internal organs (primarily the state of the cardiovascular system), to conduct a number of paraclinical research methods, among which the leading ones are neuroimaging, neuropsychological methods and methods of studying blood vessels supplying the brain.